Emerging Research in Electronics, Computer Science and Technology Proceedings of International Conference, ICERECT 2018 - Sridhar, V.; Padma, M.C.; Rao, K.A. Radhakrishna; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents the proceedings of the International Conference on Emerging Research in Electronics, Computer Science and Technology (ICERECT) organized by PES College of Engineering in Mandya. Featuring cutting-edge, peer-reviewed articles from the field of electronics, computer science and technology, it is a valuable resource for members of the scientific research community. .
An Approach for Estimation of Distance Information between Two Persons from Single 2D Image -- A Reliable Routing Protocol with Backup Scheme in Wired Computer Networks -- Anomaly-based NIDS using Artificial Neural Networks Optimized with Cuckoo Search Optimizer -- A Sequence based Machine Comprehension Modeling using LSTM and GRU -- Deep Learning based Stance Detection for Indian Social Media Text -- Class-wise Clustering for Classification of Imbalanced Text Data -- A Data Driven Model Approach for Day Wise Stock Prediction -- Performance Evaluation of Fetal ECG Extraction Algorithms -- Load Balancing for Software-defined Networks -- Web Service Ranking and Selection based on QoS -- Campus Vehicle Monitoring through Image Processing -- Assessing Human Stress through Smart Phone Usage -- Analysis of Vital Signals Acquired from Wearable Device -- A Review on Biometric Template Security -- Effective Protocols For Industrial Communication.
Keywords: Electrical engineering; Telecommunication; Signal processing; Biomedical engineering; Control engineering; Electrical and Electronic Engineering; Communications Engineering, Networks; Signal, Speech and Image Processing; Biomedical Engineering and Bioengineering; Control and Systems Theory